Environment-friendly Non-PVC floor and preparation method thereof

By combining nano-anti-bacterial materials and wear-resistant components in the transparent sheet layer, color film layer and base layer of the floor, the problem of insufficient wear resistance and antibacterial ability in the prior art is solved, and excellent sound insulation, antibacterial and wear-resistant properties of environmentally friendly Non-PVC floors are achieved.

CN119704835AActive Publication Date: 2025-03-28JIANGSU KENTIER WOOD

Patent Information

Application Number
CN202411935788.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

In the prior art, the UV coating and antibacterial properties of the floor have not been modified in combination, resulting in insufficient wear resistance and antibacterial ability of the floor.

Method used

A combined structure of transparent sheet layer, color film layer and base layer is adopted, where the transparent sheet layer contains nano-anti-bacterial materials, ultraviolet absorbers and antioxidants. The color film layer and base layer also contain corresponding antibacterial and wear-resistant components. An environmentally friendly Non-PVC floor with excellent sound insulation, antibacterial and wear-resistant properties is prepared through co-extrusion or hot pressing process.

Benefits of technology

The excellent sound insulation, antibacterial and wear resistance of the floor are achieved. The antibacterial materials of the transparent sheet layer and the floor cushion layer significantly reduce the agglomeration phenomenon of nanoparticles, improve the antibacterial ability, and the modified hemp fiber improves the mechanical strength and impact resistance of the floor cushion layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119704835A_ABST
    Figure CN119704835A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of plastic floors, and particularly relates to an environment-friendly Non-PVC floor and a preparation method thereof. The floor is sequentially provided with a transparent sheet layer, a color film layer, a backing material layer and a ground mat layer from top to bottom. The backing material layer comprises PET, PETG, calcium carbonate powder, a plasticizer, a flexibilizer, an external lubricant, an internal lubricant and oxidized wax. The transparent sheet layer and the floor mat layer adopt quaternized chitosan coated trivalent titanium-loaded nano zinc oxide as an antibacterial material and have excellent dispersity and antibacterial performance, cork particles and nano white carbon black modified fibrilia are adopted as a base material, and the sound insulation effect and the mechanical performance are improved through the floor mat layer formed by hot-pressing bonding of PP and PE.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plastic floors, and in particular relates to an environmentally friendly Non-PVC floor and a preparation method thereof. Background Art

[0002] Polyvinyl chloride (PVC) is the third largest synthetic polymer plastic in the world and is widely used in chemical, material, textile, construction and other fields. However, PVC has poor thermal stability and is easily decomposed at high temperatures to produce toxic gases, which are harmful to the environment and human body. With the global emphasis on sustainable development, more and more consumers and companies are beginning to pay attention to the environmental performance of products. Producing non-PVC flooring and using environmentally friendly materials such as polyethylene terephthalate glycol-1,4-cyclohexane dimethanol ester (PETG) will help promote the sustainable development of the industry.

[0003] The Chinese invention patent with publication number CN118958623A discloses a flame-retardant and anti-deformation PETG floor and its preparation method. The floor includes a UV coating, a wear-resistant layer, a color film layer, a substrate layer and a mute cushion layer from top to bottom; the substrate layer specifically includes the following components by weight: 40-70 parts of PETG resin, 30-55 parts of PET resin, 60-120 parts of PET recycled material, 10-20 parts of modified PET, 10-40 parts of toughening agent, 0-1.5 parts of lubricant, 200-300 parts of stone powder, 3-5 parts of antioxidant, 1-3 parts of flame retardant, 0-1 parts of chain extender, and 0-1 parts of polyamide. The invention prepares a flame-retardant and anti-deformation PETG floor with good flame retardancy, mechanical properties and anti-deformation ability by blending PET, PETG and modified PET and adding a multi-element synergistic flame retardant. However, the prior art has a technical problem that the UV coating and antibacterial properties of the floor are not modified in combination to improve the wear resistance and antibacterial ability of the floor. Summary of the invention

[0004] The purpose of the present invention is to provide an environmentally friendly Non-PVC floor and a preparation method thereof, which is used to solve the technical problem that the UV coating and antibacterial properties of the floor are not combined and modified in the prior art to improve the wear resistance and antibacterial properties of the floor.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] An environmentally friendly Non-PVC floor, which is provided with a transparent sheet layer, a color film layer, a base material layer and a floor mat layer in order from top to bottom; the thickness of the transparent sheet is 0.1-0.76 mm, the thickness of the floor mat is 0.5-5.0 mm, and the total thickness of the three layers of the transparent sheet, the color film and the base material is 1.5-6.0 mm;

[0007] The base material layer includes the following raw materials by mass: 20-30 parts of PET, 70-80 parts of PETG, 200-600 parts of calcium carbonate powder, 20-60 parts of plasticizer, 10-40 parts of toughening agent, 0-2 parts of external lubricant, 0-2 parts of internal lubricant and 0-2 parts of oxidized wax.

[0008] Preferably, the transparent sheet layer comprises the following raw materials by mass: 20 to 30 parts of PET, 70 to 80 parts of PETG, 2 to 5 parts of nano antibacterial material, 0.5 to 2 parts of ultraviolet absorber, 0.5 to 2 parts of antioxidant, 20 to 60 parts of plasticizer, 10 to 40 parts of toughening agent and 1 to 2 parts of lubricant;

[0009] The color film layer includes the following raw materials by weight: 100-110 parts of PETG, 2-8 parts of masterbatch, 0.5-2 parts of ultraviolet absorber, 0.5-2 parts of antioxidant, 20-60 parts of plasticizer, 10-40 parts of toughening agent and 0.5-2 parts of lubricant;

[0010] The floor cushion layer comprises the following raw materials by mass: 10-20 parts of PP, 4-8 parts of PE, 80-90 parts of cork particles, 2-5 parts of nano antibacterial materials, 10-20 parts of modified hemp fibers and 0.5-2 parts of lubricants.

[0011] Preferably, the total mass parts of PET and PETG in the transparent sheet layer and the base material layer are both 100 parts, and the mass ratio of PET to PETG is both 2-3:7-8; the ultraviolet absorbers of the transparent sheet layer and the color film layer are both one or more combinations of UV-234, UV-405, and UV-1300; the antioxidants of the transparent sheet layer and the color film layer are both one or more combinations of 168, 1010, and 1076; the average particle size of the cork particles in the floor mat layer is 10-20 meshes; the plasticizers of the transparent sheet layer, the color film layer, and the base material layer are all one or more combinations of epoxy soybean oil, epoxy linseed oil, and epoxy dioctyl tetrahydrophthalate, and the toughening agents are all one or more combinations of BET, ABS, and EEA; the lubricants of the transparent sheet layer, the color film layer, the base material layer, and the floor mat layer are all one or more combinations of polyethylene wax, butyl stearate, and polyethylene glycol-600.

[0012] Preferably, the method for preparing the nano antibacterial material comprises the following steps:

[0013] S21, adding 3 to 5 parts of nano zinc oxide to 30 to 50 parts of isopropanol by mass, ultrasonically dispersing for 30 to 40 minutes, and then adding 0.5 to 1 part of a surfactant to obtain a dispersion;

[0014] S22, adding 0.3-0.6 parts of titanium trichloride to 30-50 parts of isopropanol by mass, mixing evenly, then adding the dispersion, and stirring at 300-500 rpm for 30-40 min under a nitrogen atmosphere;

[0015] S23, heating the system to 180-200° C., keeping the temperature for 12-24 hours, cooling to 40-50° C., collecting the solid by centrifugation, washing with deionized water and ethanol in sequence, drying under vacuum at 60-70° C., and grinding to obtain nano zinc oxide loaded with trivalent titanium;

[0016] S24. Dissolve 1.5 to 3 parts of quaternized chitosan-100k in 50 parts of deionized water by mass, add 5 to 6 parts of nano zinc oxide loaded with trivalent titanium, ultrasonically disperse for 30 to 40 minutes, stir at 300 to 500 rpm for 12 to 24 hours, collect the solid by centrifugal filtration, dry at 60 to 70°C, and grind to obtain a nano antibacterial material.

[0017] Preferably, the surfactant in S21 is one or more combinations of pentadecyl glucoside, polyvinyl pyrrolidone and polyethylene glycol-200.

[0018] Preferably, the method for preparing the modified hemp fiber comprises the following steps:

[0019] S31, soaking 20 to 30 parts of hemp fiber in 50 to 100 parts of 5 to 10 wt % sodium hydroxide solution for 2 to 4 hours, washing with deionized water until neutral, and drying at 80 to 100° C. to obtain alkali-treated hemp fiber;

[0020] S32. Add 3 to 8 parts of KH-590 silane coupling agent by mass to 100 to 150 parts of deionized water, stir at 500 to 600 rpm at 40 to 50°C for 30 to 40 min, add 10 to 20 parts of alkali-treated hemp fiber and 1 to 3 parts of nano-silica, stir for 1 to 2 hours, filter and dry to obtain modified hemp fiber.

[0021] A method for preparing an environmentally friendly Non-PVC floor comprises the following steps:

[0022] S1. Weigh the raw materials required for each layer, pass the cork particles into 300-350°C steam for 0.5-1h, dry them at 80-100°C to control the moisture content to 6-8% as pretreatment, and cool them for use;

[0023] S2, preparing a transparent sheet layer and a color film layer: after the raw materials of the transparent sheet layer and the color film layer are uniformly mixed, the transparent sheet layer and the color film layer are successively obtained by an extruder;

[0024] S3, preparing the base material layer: after the raw materials of the base material layer are evenly mixed, the base material layer is obtained by using an internal mixer, an open mixer and calendering;

[0025] S4, preparing a floor mat layer: mixing raw materials of the floor mat layer uniformly, and hot pressing the floor mat layer at 150-170° C. for 10-15 minutes using a hot press;

[0026] S5. Bonding the Non-PVC floor substrate: hot-pressing the transparent sheet layer, the color film layer and the base material layer at 210-230° C. for 10-15 minutes by a hot press to obtain a plastic layer, applying glue to the floor mat layer, and bonding the plastic layer to obtain the Non-PVC floor substrate;

[0027] S6. Surface treatment: Coat the surface of the Non-PVC floor substrate with a UV wear-resistant primer with a thickness of 150 to 200 μm, cure it with ultraviolet radiation for 30 to 90 seconds, and punch and mill the edges to obtain the Non-PVC floor.

[0028] In the preparation method of the present invention, the transparent sheet layer, the color film layer and the base material layer can also be co-extruded to obtain the Non-PVC floor substrate.

[0029] Preferably, the extruder feed inlet temperature in S2 is 210-220°C, and the discharge port temperature is 230-250°C.

[0030] Preferably, the mixing temperature of the internal mixer in S3 is 230°C to 250°C, the mixing interval is 5 minutes, the single mixing time is 10 to 15 minutes, and the mixing temperature of the open mixer is 190°C to 220°C.

[0031] Preferably, the glue in S5 is any one of AB glue or PUR glue.

[0032] Preferably, the preparation method of the UV wear-resistant primer comprises the following steps:

[0033] S11, adding 10 to 15 parts of epoxy palm oil to 50 to 80 parts of n-heptane by mass, and then dropwise adding 20 to 30 parts of isopropanolamine, introducing nitrogen, and reacting at 70 to 100° C. for 4 to 6 hours to obtain palm oil amide polyol;

[0034] S12, by mass, react 10 to 15 parts of palm oil amide polyol and 40 to 50 parts of isophorone diisocyanate at 70 to 80° C. for 1 to 3 hours under nitrogen protection, lower the temperature to 40 to 50° C., add 10 to 15 parts of hydroxyethyl acrylate and 0.3 to 0.5 parts of p-hydroxyanisole, continue to react for 2 to 4 hours, and distill under reduced pressure to obtain modified polyurethane acrylate;

[0035] S13. Add 2 to 3 parts of photoinitiator, 0.5 to 1 part of BYK-333 leveling agent, 30 to 40 parts of polyester acrylate, 10 to 20 parts of modified polyurethane acrylate and 30 to 40 parts of isobornyl acrylate into 30 to 50 parts of anhydrous ethanol, and stir evenly to prepare a UV wear-resistant primer.

[0036] Preferably, the photoinitiator in S13 is any one or more combinations of benzoylformate, 2,2-dimethoxy-2-phenylacetophenone, and benzoyldimethylpyrrolidone.

[0037] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0038] 1. The present invention improves the preparation process and composition of each floor layer on the basis of the existing technology. The environmentally friendly Non-PVC floor prepared by the co-extrusion process or the hot pressing process has excellent sound insulation, antibacterial and wear resistance. The UV wear-resistant primer prepared by using modified polyurethane acrylate as the raw material has excellent wear resistance, flexibility and adhesion. The transparent sheet layer and the floor mat layer use quaternized chitosan coated with trivalent titanium-loaded nano zinc oxide as the antibacterial material, which has excellent dispersibility and antibacterial properties. Cork particles and hemp fibers modified by nano white carbon black are used as the base material. The floor mat layer bonded by hot pressing of PP and PE improves the sound insulation effect and mechanical properties.

[0039] 2. The UV wear-resistant primer of the present invention adopts epoxy palm oil to prepare palm oil amide polyol, and then reacts with isophorone diisocyanate and hydroxyethyl acrylate to obtain modified polyurethane acrylate with excellent wear resistance and flexibility.

[0040] 3. The nano zinc oxide loaded with trivalent titanium prepared by hydrothermal reaction of nano zinc oxide and titanium trichloride with the addition of a surfactant reduces the band gap of nano zinc oxide, increases its absorption range of visible light, and enhances its antibacterial ability. The nano zinc oxide loaded with trivalent titanium coated with quaternized chitosan can significantly reduce the agglomeration of nanoparticles and increase the life of the nano antibacterial material.

[0041] 4. The present invention uses sodium hydroxide solution to treat hemp fiber, and then uses nano-white carbon black to modify the hemp fiber, so that a uniform network structure is formed on the surface of the hemp fiber, which can effectively disperse and absorb external stress, improve the mechanical strength of the plant fiber, and enhance the interface bonding force between the hemp fiber and the cork particles and plastic, thereby improving the impact resistance of the floor mat. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 It is a schematic diagram of the hierarchical structure of the environmentally friendly Non-PVC floor of the present invention.

[0044] Explanation of the accompanying drawings: 1-transparent sheet layer, 2-color film layer, 3-base material layer, 4-ground cushion layer. DETAILED DESCRIPTION

[0045] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Example 1, see Figure 1 As shown, an environmentally friendly Non-PVC floor of this embodiment is provided with a transparent sheet layer 1, a color film layer 2, a base material layer 3 and a ground cushion layer 4 in sequence from top to bottom;

[0047] The transparent sheet layer includes the following raw materials by mass: 30 parts of PET, 70 parts of PETG, 4 parts of nano antibacterial materials, 1 part of ultraviolet absorber, 1 part of antioxidant, 60 parts of plasticizer, 40 parts of toughening agent and 2 parts of lubricant;

[0048] The color film layer includes the following raw materials by mass: 100 parts of PETG, 5 parts of masterbatch, 1 part of ultraviolet absorber, 1 part of antioxidant, 60 parts of plasticizer, 40 parts of toughening agent and 1 part of lubricant;

[0049] The base material layer includes the following raw materials by mass: 30 parts of PET, 70 parts of PETG, 600 parts of calcium carbonate powder, 60 parts of plasticizer, 40 parts of toughening agent and 2 parts of lubricant;

[0050] The floor cushion layer comprises the following raw materials in parts by mass: 20 parts of PP, 8 parts of PE, 80 parts of cork particles, 2 parts of nano-antibacterial materials, 20 parts of modified hemp fibers and 1 part of lubricant.

[0051] The thickness of the transparent sheet is 0.5 mm, the thickness of the floor mat is 3.0 mm, and the total thickness of the three layers of the transparent sheet, the color film and the base material is 3.5 mm.

[0052] The ultraviolet absorbers of the transparent sheet layer and the color film layer are both UV-234; the antioxidants of the transparent sheet layer and the color film layer are both 168; the average particle size of the cork particles of the floor mat layer is 12 meshes; the plasticizers of the transparent sheet layer, the color film layer and the base material layer are all epoxidized soybean oil, and the toughening agents are all BET; the lubricants of the transparent sheet layer, the color film layer, the base material layer and the floor mat layer are all polyethylene wax.

[0053] A method for preparing an environmentally friendly Non-PVC floor in this embodiment comprises the following steps:

[0054] S1. Weigh the raw materials required for each layer, pass the cork particles into 350°C steam for 0.5h, dry them at 100°C to control the moisture content to 6% as pretreatment, and cool them for use;

[0055] S2, preparing transparent sheet layer and color film layer: after the raw materials of transparent sheet layer and color film layer are uniformly mixed, they are sequentially passed through an extruder, the temperature of the extruder feed port is 220° C., and the temperature of the extruder discharge port is 240° C., to obtain transparent sheet layer and color film layer;

[0056] S3, preparing the base material layer: after the raw materials of the base material layer are evenly mixed, the base material layer is obtained by using an internal mixer, an open mixer and calendering, the mixing temperature of the internal mixer is 230°C, the mixing interval is 5min, the single mixing time is 15min, and the mixing temperature of the open mixer is 220°C;

[0057] S4, preparing a floor mat layer: mixing raw materials of the floor mat layer uniformly, and hot pressing the raw materials at 170° C. for 10 minutes using a hot press to prepare the floor mat layer;

[0058] S5. Bonding the Non-PVC floor substrate: hot-pressing the transparent sheet layer, the color film layer and the base material layer at 230° C. for 10 minutes by a hot press to obtain a plastic layer, coating the floor mat layer with PUR glue, and bonding the plastic layer to obtain the Non-PVC floor substrate;

[0059] S6. Surface treatment: Coat the surface of the Non-PVC floor substrate with a UV wear-resistant primer with a thickness of 200 μm, cure it with ultraviolet radiation for 60 seconds, and punch and mill the edges to obtain the Non-PVC floor.

[0060] The preparation method of the UV wear-resistant primer of the present embodiment comprises the following steps:

[0061] S11, adding 15 parts of epoxy palm oil to 60 parts of n-heptane by mass, and then dropping 30 parts of isopropanolamine, introducing nitrogen, and reacting at 100° C. for 5 hours to obtain palm oil amide polyol;

[0062] S12, by mass, reacting 15 parts of palm oleamide polyol and 45 parts of isophorone diisocyanate at 80° C. for 2 h under nitrogen protection, lowering the temperature to 40° C., adding 10 parts of hydroxyethyl acrylate and 0.4 parts of p-hydroxyanisole, and continuing the reaction for 2 h, and distilling under reduced pressure to obtain modified polyurethane acrylate;

[0063] S13. Add 3 parts of benzoyl formate photoinitiator, 1 part of BYK-333 leveling agent, 40 parts of polyester acrylate, 20 parts of modified polyurethane acrylate and 40 parts of isobornyl acrylate to 50 parts of anhydrous ethanol, and stir evenly to prepare a UV wear-resistant primer.

[0064] The method for preparing the nano antibacterial material of this embodiment comprises the following steps:

[0065] S21, adding 3 parts of nano zinc oxide to 40 parts of isopropanol by mass, and adding 0.7 parts of polyvinyl pyrrolidone after ultrasonic dispersion for 40 minutes to obtain a dispersion;

[0066] S22, adding 0.6 parts of titanium trichloride to 50 parts of isopropanol by mass, mixing well, then adding the dispersion, and stirring at 400 rpm for 40 minutes under a nitrogen atmosphere;

[0067] S23, heating the system to 200°C, keeping the temperature for 24 hours, cooling to 50°C, collecting the solid by centrifugation, washing with deionized water and ethanol in sequence, drying under vacuum at 70°C, and grinding to obtain nano zinc oxide loaded with trivalent titanium;

[0068] S24. Dissolve 3 parts of quaternized chitosan-100k in 50 parts of deionized water by mass, add 5 parts of nano zinc oxide loaded with trivalent titanium, ultrasonically disperse for 30 minutes, stir at 500 rpm for 24 hours, collect the solid by centrifugal filtration, dry at 60°C, and grind to obtain a nano antibacterial material.

[0069] The method for preparing the modified hemp fiber of this embodiment comprises the following steps:

[0070] S31, soaking 20 parts of hemp fiber in 50 parts of 10wt% sodium hydroxide solution for 2h, washing with deionized water until neutral, and drying at 80°C to obtain alkali-treated hemp fiber;

[0071] S32. Add 3 parts of KH-590 silane coupling agent to 100 parts of deionized water by mass, stir at 500 rpm at 40°C for 30 min, add 15 parts of alkali-treated hemp fiber and 3 parts of nano-silica, stir for 2 h, filter and dry to obtain modified hemp fiber.

[0072] Example 2, see Figure 1As shown, an environmentally friendly Non-PVC floor of this embodiment is provided with a transparent sheet layer, a color film layer, a base material layer and a floor cushion layer in sequence from top to bottom;

[0073] The transparent sheet layer includes the following raw materials by weight: 20 parts of PET, 80 parts of PETG, 3 parts of nano antibacterial material, 0.5 parts of ultraviolet absorber, 1 part of antioxidant, 30 parts of plasticizer, 20 parts of toughening agent and 1 part of lubricant;

[0074] The color film layer includes the following raw materials by mass: 110 parts of PETG, 8 parts of masterbatch, 1 part of ultraviolet absorber, 1 part of antioxidant, 30 parts of plasticizer, 20 parts of toughening agent and 1 part of lubricant;

[0075] The base material layer includes the following raw materials by mass: 20 parts of PET, 80 parts of PETG, 300 parts of calcium carbonate powder, 30 parts of plasticizer, 20 parts of toughening agent and 1 part of lubricant;

[0076] The floor cushion layer comprises the following raw materials in parts by mass: 20 parts of PP, 8 parts of PE, 80 parts of cork particles, 2 parts of nano-antibacterial materials, 20 parts of modified hemp fibers and 1 part of lubricant.

[0077] The thickness of the transparent sheet is 0.1 mm, the thickness of the floor mat is 5.0 mm, and the total thickness of the three layers of the transparent sheet, the color film and the base material is 1.5 mm.

[0078] The ultraviolet absorber of the transparent sheet layer and the color film layer is UV-405; the antioxidant of the transparent sheet layer and the color film layer is 1010; the average particle size of the cork particles of the floor cushion layer is 20 meshes; the plasticizers of the transparent sheet layer, the color film layer and the base material layer are all epoxy linseed oil, and the toughening agents are all ABS; the lubricants of the transparent sheet layer, the color film layer, the base material layer and the floor cushion layer are all polyethylene glycol-600.

[0079] A method for preparing an environmentally friendly Non-PVC floor in this embodiment comprises the following steps:

[0080] S1. Weigh the raw materials required for each layer, pass the cork particles through 350°C steam for 1 hour, dry them at 100°C to control the moisture content to 8% as pretreatment, and cool them for use;

[0081] S2, preparing transparent sheet layer and color film layer: after the raw materials of transparent sheet layer and color film layer are uniformly mixed, they are sequentially passed through an extruder, the temperature of the extruder feed port is 210° C., and the temperature of the discharge port is 230° C., to obtain transparent sheet layer and color film layer;

[0082] S3, preparing the base material layer: after the raw materials of the base material layer are evenly mixed, the base material layer is obtained by using an internal mixer, an open mixer and calendering. The mixing temperature of the internal mixer is 230° C., the mixing interval is 5 min, the single mixing time is 15 min, and the mixing temperature of the open mixer is 215° C.;

[0083] S4, preparing a floor mat layer: mixing raw materials of the floor mat layer uniformly, and hot pressing the raw materials at 170° C. for 10 minutes using a hot press to prepare the floor mat layer;

[0084] S5. Bonding the Non-PVC floor substrate: hot-pressing the transparent sheet layer, the color film layer and the base material layer at 220° C. for 10 minutes by a hot press to obtain a plastic layer, coating the floor mat layer with PUR glue, and bonding the plastic layer to obtain the Non-PVC floor substrate;

[0085] S6. Surface treatment: Coat the surface of the Non-PVC floor substrate with a UV wear-resistant primer with a thickness of 200 μm, cure it with ultraviolet radiation for 60 seconds, and punch and mill the edges to obtain the Non-PVC floor.

[0086] The preparation method of the UV wear-resistant primer and the modified hemp fiber in this embodiment is the same as the preparation method in Example 1.

[0087] The difference between the nano antibacterial material of this embodiment and that of embodiment 1 is that the surfactant is replaced by pentadecyl glycoside.

[0088] Example 3, see Figure 1 As shown, an environmentally friendly Non-PVC floor of this embodiment is provided with a transparent sheet layer, a color film layer, a base material layer and a floor cushion layer in sequence from top to bottom;

[0089] The transparent sheet layer includes the following raw materials by weight: 25 parts of PET, 75 parts of PETG, 4 parts of nano antibacterial material, 0.5 parts of ultraviolet absorber, 1 part of antioxidant, 60 parts of plasticizer, 40 parts of toughening agent and 2 parts of lubricant;

[0090] The color film layer includes the following raw materials by mass: 110 parts of PETG, 5 parts of masterbatch, 1 part of ultraviolet absorber, 1 part of antioxidant, 60 parts of plasticizer, 40 parts of toughening agent and 2 parts of lubricant;

[0091] The base material layer includes the following raw materials by mass: 25 parts of PET, 75 parts of PETG, 200 parts of calcium carbonate powder, 60 parts of plasticizer, 40 parts of toughening agent and 2 parts of lubricant;

[0092] The floor cushion layer comprises the following raw materials in parts by mass: 20 parts of PP, 8 parts of PE, 80 parts of cork particles, 2 parts of nano-antibacterial materials, 20 parts of modified hemp fibers and 2 parts of lubricants.

[0093] The thickness of the transparent sheet is 0.76 mm, the thickness of the floor mat is 1.0 mm, and the total thickness of the three layers of the transparent sheet, the color film and the base material is 5.5 mm.

[0094] The ultraviolet absorber of the transparent sheet layer and the color film layer is UV-1300; the antioxidant of the transparent sheet layer and the color film layer is 1076; the average particle size of the cork particles of the floor cushion layer is 16 mesh; the plasticizers of the transparent sheet layer, the color film layer and the base material layer are dioctyl epoxide tetrahydrophthalate, and the toughening agents are EEA; the lubricants of the transparent sheet layer, the color film layer, the base material layer and the floor cushion layer are butyl stearate.

[0095] A method for preparing an environmentally friendly Non-PVC floor in this embodiment comprises the following steps:

[0096] S1. Weigh the raw materials required for each layer, pass the cork particles through 300°C steam for 1 hour, dry them at 90°C to control the moisture content to 8% as pretreatment, and cool them for use;

[0097] S2, preparing transparent sheet layer and color film layer: after the raw materials of transparent sheet layer and color film layer are uniformly mixed, they are sequentially passed through an extruder, the temperature of the extruder feed port is 215° C., and the temperature of the discharge port is 235° C., to obtain transparent sheet layer and color film layer;

[0098] S3, preparing the base material layer: after the raw materials of the base material layer are evenly mixed, the base material layer is obtained by using an internal mixer, an open mixer and calendering, the mixing temperature of the internal mixer is 235°C, the mixing interval is 5min, the single mixing time is 15min, and the mixing temperature of the open mixer is 220°C;

[0099] S4, preparing a floor mat layer: mixing raw materials of the floor mat layer uniformly, and hot pressing the raw materials at 170° C. for 10 minutes using a hot press to prepare the floor mat layer;

[0100] S5. Bonding the Non-PVC floor substrate: hot-pressing the transparent sheet layer, the color film layer and the base material layer at 215° C. for 15 minutes by a hot press to obtain a plastic layer, coating the floor mat layer with AB glue, and bonding the plastic layer to obtain the Non-PVC floor substrate;

[0101] S6. Surface treatment: Coat the surface of the Non-PVC floor substrate with a UV wear-resistant primer with a thickness of 180 μm, cure it with ultraviolet radiation for 90 seconds, and punch and mill the edges to obtain the Non-PVC floor.

[0102] The preparation method of the nano antibacterial material of this embodiment is the same as the preparation method of embodiment 1.

[0103] The difference between the UV wear-resistant primer of this embodiment and that of Embodiment 1 is that the photoinitiator is replaced by benzoyl dimethyl pyrrolidone.

[0104] The difference between the modified hemp fiber of this embodiment and that of embodiment 1 is that the alkali treatment step in S31 is replaced by soaking in 100 parts of 5 wt % sodium hydroxide solution for 4 hours.

[0105] Comparative Example 1: The difference between this comparative example and Example 1 is that palm oil amide polyol is replaced by polycaprolactone polyol.

[0106] Comparative Example 2: This comparative example differs from Example 1 in that quaternized chitosan-100k is replaced by polyacrylamide.

[0107] Comparative Example 3: The difference between this comparative example and Example 1 is that the hemp fiber is not treated by soaking in sodium hydroxide solution.

[0108] Performance Testing

[0109] According to GB50118-2010 "Code for Sound Insulation Design of Civil Buildings", a reference floor is established, hollow blocks are used as the reference floor, the thickness of the reference floor is set to 150 mm, and each side is covered with environmentally friendly Non-PVC flooring. The weighted impact sound pressure level of the hollow blocks not covered with environmentally friendly Non-PVC flooring is 86 dB, and the weighted impact sound pressure level of the floors obtained in each embodiment and comparative example is measured.

[0110] The wear rates of the floors prepared in the examples and comparative examples were measured according to GB3960-83 “Test methods for sliding friction and wear of plastics”.

[0111] The tensile strength and elongation at break of the floors prepared in each embodiment and comparative example were measured according to GB / T 1040.2-2022 “Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics”.

[0112] According to GB / T 21866-2008 "Determination of antibacterial properties and antibacterial effects of antibacterial coatings (paint films)", the floor samples containing only PETG were used as blank control groups. The floor samples were sterilized by ultraviolet irradiation for 3 hours. The Escherichia coli strains were activated and prepared to a concentration of 3×10 4 cfu / ml bacterial suspension; place the sample in the bacterial suspension, shake at 300r / min for 5min at room temperature, take 1ml of the bacterial suspension and dilute it to 100 times, take 1ml of the diluted bacterial suspension and evenly smear the sample and place it in a sterilized plate, and culture it at 38℃ and relative humidity greater than 90% for 24h. Then add washing solution to wash repeatedly, take the washing solution and inoculate it in nutrient agar medium, continue to culture at 38℃ for 24h, count the colonies, and calculate the antibacterial rate by the following formula.

[0113]

[0114] R——inhibition rate, %;

[0115] B——average colony count of blank control group;

[0116] C——Average colony count of the sample.

[0117] The test results are shown in Table 1 below:

[0118] Table 1

[0119]

[0120] It can be seen from the data in the table that in Comparative Example 1, the wear resistance of the UV wear-resistant primer is deteriorated due to the replacement of palm oil amide polyol with polycaprolactone polyol. In Comparative Example 2, the quaternized chitosan-100k is replaced with polyacrylamide, which inhibits the antibacterial performance of the nano-antibacterial material, and the antibacterial rate is only 61.3%. In Comparative Example 3, the hemp fiber is not treated with alkali, which weakens its adhesion to the floor cushion layer. Therefore, the tensile strength and elongation at break have a slight downward trend, indicating that the environmentally friendly Non-PVC floor prepared by the present invention has excellent sound insulation, antibacterial and wear resistance.

[0121] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0122] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. An environmentally friendly Non-PVC floor, characterized in that: A transparent sheet layer, a color film layer, a base material layer and a ground pad layer are sequentially arranged from top to bottom; the thickness of the transparent sheet is 0.1 to 0.76 mm, the thickness of the ground pad is 0.5 to 5.0 mm, and the total thickness of the three layers of the transparent sheet, the color film and the base material is 1.5 to 6.0 mm; The base material layer includes the following raw materials by mass: 20-30 parts of PET, 70-80 parts of PETG, 200-600 parts of calcium carbonate powder, 20-60 parts of plasticizer, 10-40 parts of toughening agent, 0-2 parts of external lubricant, 0-2 parts of internal lubricant and 0-2 parts of oxidized wax.

2. The environmentally friendly Non-PVC floor according to claim 1, characterized in that: The transparent sheet layer comprises the following raw materials by weight: 20 to 30 parts of PET, 70 to 80 parts of PETG, 2 to 5 parts of nano antibacterial material, 0.5 to 2 parts of ultraviolet absorber, 0.5 to 2 parts of antioxidant, 20 to 60 parts of plasticizer, 10 to 40 parts of toughening agent and 1 to 2 parts of lubricant; The color film layer includes the following raw materials by weight: 100-110 parts of PETG, 2-8 parts of masterbatch, 0.5-2 parts of ultraviolet absorber, 0.5-2 parts of antioxidant, 20-60 parts of plasticizer, 10-40 parts of toughening agent and 0.5-2 parts of lubricant; The floor cushion layer comprises the following raw materials by mass: 10-20 parts of PP, 4-8 parts of PE, 80-90 parts of cork particles, 2-5 parts of nano antibacterial materials, 10-20 parts of modified hemp fibers and 0.5-2 parts of lubricants.

3. The environmentally friendly Non-PVC floor according to claim 2, characterized in that: The total mass parts of PET and PETG in the transparent sheet layer and the base material layer are both 100 parts, and the mass ratio of PET to PETG is both 2-3:7-8; the ultraviolet absorbers of the transparent sheet layer and the color film layer are both one or more combinations of UV-234, UV-405, and UV-1300; the antioxidants of the transparent sheet layer and the color film layer are both one or more combinations of 168, 1010, and 1076; the average particle size of the cork particles in the floor mat layer is 10-20 meshes; the plasticizers of the transparent sheet layer, the color film layer, and the base material layer are all one or more combinations of epoxy soybean oil, epoxy linseed oil, and epoxy dioctyl tetrahydrophthalate, and the toughening agents are all one or more combinations of BET, ABS, and EEA; the lubricants of the transparent sheet layer, the color film layer, the base material layer, and the floor mat layer are all one or more combinations of polyethylene wax, butyl stearate, and polyethylene glycol-600.

4. The environmentally friendly Non-PVC floor according to claim 2, characterized in that: The preparation method of the nano antibacterial material comprises the following steps: S21, adding 3 to 5 parts of nano zinc oxide to 30 to 50 parts of isopropanol by mass, ultrasonically dispersing for 30 to 40 minutes, and then adding 0.5 to 1 part of a surfactant to obtain a dispersion; S22, adding 0.3-0.6 parts of titanium trichloride to 30-50 parts of isopropanol by mass, mixing evenly, then adding the dispersion, and stirring at 300-500 rpm for 30-40 min under a nitrogen atmosphere; S23, heating the system to 180-200° C., keeping the temperature for 12-24 hours, cooling to 40-50° C., collecting the solid by centrifugation, washing with deionized water and ethanol in sequence, drying under vacuum at 60-70° C., and grinding to obtain nano zinc oxide loaded with trivalent titanium; S24. Dissolve 1.5 to 3 parts of quaternized chitosan-100k in 50 parts of deionized water by mass, add 5 to 6 parts of nano zinc oxide loaded with trivalent titanium, ultrasonically disperse for 30 to 40 minutes, stir at 300 to 500 rpm for 12 to 24 hours, collect the solid by centrifugal filtration, dry at 60 to 70°C, and grind to obtain a nano antibacterial material.

5. The environmentally friendly Non-PVC floor according to claim 4, characterized in that: The surfactant in S21 is one or more combinations of pentadecyl glucoside, polyvinyl pyrrolidone, and polyethylene glycol-200.

6. The environmentally friendly Non-PVC floor according to claim 2, characterized in that: The method for preparing the modified hemp fiber comprises the following steps: S31, soaking 20 to 30 parts of hemp fiber in 50 to 100 parts of 5 to 10 wt % sodium hydroxide solution for 2 to 4 hours, washing with deionized water until neutral, and drying at 80 to 100° C. to obtain alkali-treated hemp fiber; S32. Add 3 to 8 parts of KH-590 silane coupling agent by mass to 100 to 150 parts of deionized water, stir at 500 to 600 rpm at 40 to 50°C for 30 to 40 min, add 10 to 20 parts of alkali-treated hemp fiber and 1 to 3 parts of nano-silica, stir for 1 to 2 hours, filter and dry to obtain modified hemp fiber.

7. A method for preparing an environmentally friendly Non-PVC floor, characterized in that: The steps include: S1. Weigh the raw materials required for each layer, pass the cork particles into 300-350°C steam for 0.5-1h, dry them at 80-100°C to control the moisture content to 6-8% as pretreatment, and cool them for use; S2, preparing a transparent sheet layer and a color film layer: after the raw materials of the transparent sheet layer and the color film layer are uniformly mixed, the transparent sheet layer and the color film layer are successively obtained by an extruder; S3, preparing the base material layer: after the raw materials of the base material layer are evenly mixed, the base material layer is obtained by using an internal mixer, an open mixer and calendering; S4, preparing a floor mat layer: mixing raw materials of the floor mat layer uniformly, and hot pressing the floor mat layer at 150-170° C. for 10-15 minutes using a hot press; S5. Bonding the Non-PVC floor substrate: hot-pressing the transparent sheet layer, the color film layer and the base material layer at 210-230° C. for 10-15 minutes by a hot press to obtain a plastic layer, applying glue to the floor mat layer, and bonding the plastic layer to obtain the Non-PVC floor substrate; S6. Surface treatment: Coat the surface of the Non-PVC floor substrate with a UV wear-resistant primer with a thickness of 150 to 200 μm, cure it with ultraviolet radiation for 30 to 90 seconds, and punch and mill the edges to obtain the Non-PVC floor.

8. The method for preparing an environmentally friendly Non-PVC floor according to claim 7, characterized in that: The extruder feed inlet temperature of the S2 is 200-220°C, and the discharge port temperature is 230-250°C; the mixing temperature of the internal mixer of the S3 is 230-250°C, the mixing interval is 5-10 minutes, the single mixing time is 10-20 minutes, and the mixing temperature of the open mixer is 190-220°C; the glue in the S5 is either AB glue or PUR glue.

9. The method for preparing an environmentally friendly Non-PVC floor according to claim 7, characterized in that: The preparation method of the UV wear-resistant primer comprises the following steps: S11, adding 10 to 15 parts of epoxy palm oil to 50 to 80 parts of n-heptane by mass, and then dropwise adding 20 to 30 parts of isopropanolamine, introducing nitrogen, and reacting at 70 to 100° C. for 4 to 6 hours to obtain palm oil amide polyol; S12, by mass, react 10 to 15 parts of palm oil amide polyol and 40 to 50 parts of isophorone diisocyanate at 70 to 80° C. for 1 to 3 hours under nitrogen protection, lower the temperature to 40 to 50° C., add 10 to 15 parts of hydroxyethyl acrylate and 0.3 to 0.5 parts of p-hydroxyanisole, continue to react for 2 to 4 hours, and distill under reduced pressure to obtain modified polyurethane acrylate; S13. Add 2 to 3 parts of photoinitiator, 0.5 to 1 part of BYK-333 leveling agent, 30 to 40 parts of polyester acrylate, 10 to 20 parts of modified polyurethane acrylate and 30 to 40 parts of isobornyl acrylate into 30 to 50 parts of anhydrous ethanol, and stir evenly to prepare a UV wear-resistant primer.

10. The method for preparing an environmentally friendly Non-PVC floor according to claim 9, characterized in that: The photoinitiator in S13 is any one or more combinations of benzoylformate, 2,2-dimethoxy-2-phenylacetophenone, and benzoyl dimethyl pyrrolidone.

Citation Information

Patent Citations

  • Nano-wood plastic composite material and preparation method thereof

    CN108976645A

  • Plastic master batch based on polypropylene modification and preparation process of plastic master batch

    CN110684275A

  • Application of black titanium dioxide material in dark environment

    CN118161521A

  • Preparation method of degradable tableware hydrophobic coating

    CN118772471A

  • Flame-retardant anti-deformation PETG floor and preparation method thereof

    CN118958623A

Cited By

  • Heat-insulating high-strength plastic floor and preparation method thereof

    CN121295891A